Labor Policy to Promote Good Jobs in Tunisia : Revisiting Labor Regulation, Social Security, and Active Labor Market Programs - Angel-Urdinola, Diego F. (Washington, DC: World Bank, 2014)
Tunisians are striving for the opportunity to realize their potential and aspirations in a country that is rich in both human and physical capital, but whose recent economic growth has failed to create enough opportunities in the form of good and productive jobs. This report highlights the main barriers that hinder the Tunisian labor market from providing income, protection, and prosperity to its citizens and proposes a set of labor policies that could facilitate the creation of better, more inclusive, and more productive jobs. The weak economic performance and insufficient and low-quality job creation in Tunisia is primarily the result of an economic environment permeated by distortions, barriers to competition, and excessive red tape, including in the labor market. This has resulted in the creation of a insufficient number of jobs, especially in the formal sector. To change this situation, policy makers need to address five strategic directives that can promote long-term inclusive growth and formality: foster competition; realign incentives, pay, and benefit packages in the public sector; move toward labor regulations that promote labor mobility and provide support to workers in periods of transition; enhance the productivity of informal workers through training and skills building; and reform existing social insurance systems and introduce new instruments to attain broader coverage.